2015
DOI: 10.1242/jeb.127910
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the cost of locomotion with inclined trunk predicts crouched leg kinematics of small birds at realistic levels of elastic recoil

Abstract: Small birds move with pronograde trunk orientation and crouched legs. Although the pronograde trunk has been suggested to be beneficial for grounded running, the cause(s) of the specific leg kinematics are unknown. Here we show that three charadriiform bird species (northern lapwing, oystercatcher, and avocet; great examples of closely related species that differ remarkably in their hind limb design) move their leg segments during stance in a way that minimizes the cost of locomotion. We imposed measured trunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have indicated that terrestrial locomotion in modern birds is considerably different from that in humans. Birds employ a crouched, digitigrade, parasagittal posture, whereby the femur is subhorizontally oriented for much of the stride, and where the majority of limb movement occurs at the knee, driven by the ‘hamstring’ muscles [ 19 – 33 ]. This reflects the location of their whole-body centre of mass (COM), which is markedly anterior to the hips [ 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that terrestrial locomotion in modern birds is considerably different from that in humans. Birds employ a crouched, digitigrade, parasagittal posture, whereby the femur is subhorizontally oriented for much of the stride, and where the majority of limb movement occurs at the knee, driven by the ‘hamstring’ muscles [ 19 – 33 ]. This reflects the location of their whole-body centre of mass (COM), which is markedly anterior to the hips [ 31 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a reaction force, it represents the summation of accelerations of all the individual components of the body during movement, and is fundamental to understanding the forces, moments and stresses occurring within the limbs of an animal during locomotion [ 7 , 35 , 51 56 ]. Despite its importance, the GRF has been measured in relatively few species of birds, in the course of investigating other biomechanical parameters [ 26 , 30 , 33 , 35 , 37 , 40 , 46 , 53 , 57 – 61 ]. Hence, not enough is currently known about how the GRF varies in time and space throughout the stance phase in different bird species, or how this varies with speed or body size, to the point that quantitative predictions may be made for other theropods (avian or non-avian).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using monkeys have reported differences in bipedal and quadrupedal walking (Japanese macaque [ 7 10 ], bonobo [ 11 ], reviewed in [ 12 ]) and the evolution of human walking (chimpanzee [ 13 ], reviewed in [ 14 ]). Studies using birds have discussed the energetic effect required for the transition from walking to running (guinea fowl [ 15 ], emu and ostrich [ 16 ], lapwing, oystercatcher, and avocet [ 17 ]). Moreover, animal models of neural ataxia, such as monkey models of Parkinson’s disease (transgenic [ 18 , 19 ], neurotoxin [ 20 ], reviewed in [ 21 , 22 ]), stroke (reviewed in [ 23 ]), and spinal cord injury have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Further, alternative hypotheses relating to the implications of elbow/knee orientation concerning directional stability [43] or passive release of elastic energy facilitating protraction [44] should not be dismissed, especially for highly cursorial quadrupeds. And multi-segment limbs may well offer multiple advantages, from facilitating elastic storage and recoil (see [13]) with implications in terms of passive joint stabilization (Seyfarth et al, 2001 [45]). However, the benefit proposed here of reduction in joint work given a generally low limb-work force profile appears potentially very general, and applicable to parasagittal quadrupeds of diverse scales, evolutionary backgrounds (consider chameleon), and even orientations (remember sloth).…”
Section: General Conclusionmentioning
confidence: 99%
“…This was attributed to an absence-or at least insufficiency-of multi-joint linkages to provide inter-joint power transfer [11], meaning that minimization of joint work was taken as a suitable initial cost function to consider when exploring animal limb design (though see also [12]). Minimization of joint work does appear effective in accounting for some features of bipedal [13] and quadrupedal [14,15] gait kinetics [1]. But force vectors in bipeds (humans: [16]; birds: [17]; wallabies: [18]) and quadrupeds [19] are consistently observed to be orientated between axial and vertical.…”
Section: Paper Scopementioning
confidence: 99%